THE ROLE OF DYNAMIC CAPABILITIES IN THE INTERNATIONALIZATION OF MEDIUM SIZED FINNISH MANUFACTURING FIRMS - A case for Sormat Oy - Muli, David (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
A rapidly changing business environment has necessitated most small and medium sized enterprises with international ambitions to reconsider their sources of competitive advantage. To survive in the face of a changing business environment, firms should utilize their dynamic organizational capabilities as well as their internationalization capabilities. Firms develop a competitive advantage if they can exploit their unique organizational competences in a new or foreign market and also if they can acquire new capabilities as a result of engaging in foreign markets. The acquired capabilities from foreign locations enhance the existing capability portfolio of a firm with a desire to internationalize. The study combined the research streams of SME organizational dynamic capability and internationalization capability to build a complete picture on the existing knowledge. An intensive case study was used for empirically testing the theoretical framework of the study and compared with the literature on various organizational capability factors and internationalization capabilities. Sormay Oy was selected because it is a successful medium sized company operating in Finland in the manufacturing industry which has a high international profile. In addition, it has sufficient rate of growth in sales that warrants it to engage internationally in matters such as, acquisitions, joint ventures and partnerships. The key findings of the study suggests that, medium sized manufacturing firms have a set of core competences arising from their organizational capabilities which were identified to be employee know how and relationship with stakeholders which aid the firm in its quest for attaining competitive advantage, ensuring production flexibility and gaining benefits present in a network. In addition, internationalization capabilities were identified under both the RAT test and CAT test whereby the primary findings suggests that, firms that outperform their competitors produce products that meet specific customer and country requirements, foresee the pitfalls of imitation brought about by the foreign local companies and members of a particular network through joint ventures, acquisitions or partnerships as well as those firms that are capable to acquire new capabilities in the foreign markets and successfully use these acquired capabilities to enhance or renew their capability portfolio for their competitive advantage. Additional significant findings under internationalization capabilities were discovered whereby, Sormay Oy was able to develop a new market space for its products despite the difficult institutional environment present in Russia.